Digital Based Administration Service in Ngrendeng and Banjarsari Villages, Selorejo District, Blitar - Dewi, Candra; Astuti, Ani Budi; Nuh, Mohammad; Rifan, Mohamad (Journal of Innovation and Applied Technology, 2025)
In facing the challenges of the digital era, Ngrendeng and Banjarsari villages need innovative approaches to improve the efficiency of public services. This activity aims to increase the understanding and ability of village officials and village residents about digital-based village administration services. The application was built by utilizing some technologies that are WhatsApp Chatbot, Google Drive and Google Form. The needs analysis shows that there are differences in service facilities between the two villages, where Banjarsari only focuses on providing information regarding the requirements for submitting certificates, while Ngrendeng allows for digital processing of letters at the same time. The evaluation of the questionnaire shows that the application developed is very appropriate to needs. This activity is published in national mass media Radar Malang, Prasetya Online UB, and Academiamu. In addition, the training module has been registered Intellectual Property Rights to the Indonesian Ministry of Law and Human Rights.